Direct dark matter research by observing electrons produced in neutralino-nucleus collisions - Moustakidis, Ch. C.; Vergados, J. D.; Ejiri, H. (HNPS Advances in Nuclear Physics, 2019)
The most important process for directly detecting dark matter is the LSP-nucleus elastic scattering by measuring the energy of the recoiling nucleus. In the present work we explore a novel process that is the detection of the dark matter constituents by observing the low energy ionization electrons. We develop the formalism and apply it in calculating the ratio of the ionization rate to the nuclear recoil rate in a variety of atoms. The obtained ratios are essentially independent of all parameters of supersymmetry except the neutralino mass, but they crucially depend on the electron energy cut off. Based on our results it is both interesting and realistic to detect the LSP by measuring the ionization electrons following the-LSP nuclear collisions.